Development of a novel lightweight media for Biological Aerated Filters (BAFS) - Moore, R.; Quarmby, Joanne; Stephenson, Tom (Cranfield University, School of Water Sciences, 1999)
Clay has been foamed and extruded using novel technology, to produce a lightweight media called StarLight C. Altering the production process parameters allows control of the media diameter, density, strength, and surface roughness. In its application as a Biological Aerated Filter (BAF) media, a low density may be advantageous since this will reduce the minimum fluidisation velocity (Vmf) of the media. Consequently a lower liquid velocity will be required during filter backwashing, which could reduce the operating costs and increase the productivity of the reactor. This paper reports the performance of StarLight C and standard expanded clay (media A) as media in pilot scale BAFs treating settled sewage with hydraulic residence times between 58 and 96 minutes. The BAFs were backwashed every 24 hours at a liquid flow rate corresponding to 40% of the Vmf of the media. The BAF using StarLight C required approximately half the volume of backwash water needed by the BAF filled with media A. To optimise the performance of BAFs further the filter run time should be maximised. This requires the media size and voidage to be maximised without compromising filtration efficiency.